Crystallographic and Colorimetric Analysis of Dental Enamel - Ljiljana Tihaček-Šojić; Vladimir Milićević; Marija Đurić-Srejić (Dental Anthropology Association, 1997)
Tooth color and the correlation of the composition of dental enamel with color were investigated in samples of teeth from two medieval Serb cemeteries. Differences in the composition of apatite crystals in the dental enamel of the two samples were found. Color ranges of teeth from the two samples differ in hues and chromas. This result suggests that enamel composition may have an influence on the color of teeth. The prevalence of chlorapatite in enamel causes tooth color to be closer to red and of higher chroma than teeth whose enamel consists of hydroxylapatite. No evidence indicated that soil ingredients were incorporated into the dental enamel of either sample.